Criminal Geography as a New Subject in the Hungarian Higher Education - Sallai, János; Mátyás, Szabolcs (Magyar Rendészet, 2016)
Criminal geography as a discipline has a three-decade long history in Hungary. It is a welcome fact that the number of publications dealing with criminal geography has increased, it is already taught at universities and soon the university textbook of the subject will be finished. Hopefully, this favourable trend will continue and criminal geography will become a widely-respected and studied discipline which will contribute to the decrease of criminal acts.